Adaptation and validation of the Ethical Conflict Nursing Questionnaire-Critical Care Version to Italian language - Bonetti, Loris; Terzoni, Stefano; Ferrara, Paolo; Destrebecq, Anne; Zuriguel-Pérez, Esperanza; Falcó-Pegueroles, Anna (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the workEthical conflict in Intensive Care Unit (ICU) can lead to poor quality health care and attention. Knowing the level of exposure to ethical conflict in health professionals allows to design strategies for improve the ethical environments and making decisions process. To study ethical conflict in health professionals it is necessary to have valid and reliable instruments that can be applied to different health and cultural contexts. No tool existed in Italian context still now. Therefore, the aim of this study was to adapt and validate the Ethical Conflict Nursing Questionnaire-Critical Care Version to the Italian sociocultural context.MethodsThis is a two-phase psychometric study, including one translation-back-translation phase, and an analysis phase for determining the content and construct validity, by means respectively Content Validity Index, Principal Component Analysis (PCA) and Confirmatory Factor Analysis(CFA), and reliability of the instrument, by means Cronbach's α calculation.ResultsThe sample included 286 nurses from critical care units of four hospitals in (deleted for review) (Italy). Translation-back-translation phase was successful. A Content Validity Index of 95.39 was obtained. The overall Cronbach's α value was 0.866. When an item was eliminated, this value oscillated between 0.871 and 0.881. As the original tool, Principal Component Analysis (PCA) and Confirmatory Factor Analysis (CFA) confirmed a single factor capable of explaining more than 30% of the variance.ConclusionsThe ECNQ-CCV Italian version is a valid and reliable instrument for measuring the exposure of ICU nursing professionals to ethical conflict.